Circadian Rhythm Sleep Disorders: Genetics, Mechanisms, and Adverse Effects on Health - Liu, Chaoran; Tang, Xiangrong; Gong, Zishan; Zeng, Wang; Hou, Qiao; Lu, Renbin (Frontiers in Genetics, 2022)
Nearly all living organisms, from cyanobacteria to humans, have an internal circadian oscillation with a periodicity of approximately 24 hours. In mammals, circadian rhythms regulate diverse physiological processes including the body temperature, energy metabolism, immunity, hormone secretion, and daily sleep-wake cycle. Sleep is tightly regulated by circadian rhythms, whereas a misalignment between the circadian rhythms and external environment may lead to circadian rhythm sleep disorders (CRSD). CRSD includes four main kinds of disorders: the advanced sleep-wake phase disorder (ASPD), the delayed sleep-wake phase disorder (DSPD), the irregular sleep-wake rhythm disorder and the non-24-hour sleep-wake rhythm disorder. Recent studies have begun to shed light on the genetic basis of CRSD. Deciphering the genetic codes for ASPD and DSPD has so far been more successful than the other CRSDs, which allow for the development of animal models and understanding of the pathological mechanisms for these disorders. And studies from humans or animal models implicate CRSDs are associated with adverse health consequences, such as cancer and mental disorders. In this review, we will summarize the recent advances in the genetics, underlying mechanisms and the adverse effects on health of ASPD and DSPD.